PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA KELAS VB SD NEGERI 110 PEKANBARU - Resti Zulianti; Lazim N; Jaya Adiputra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The 2013 curriculum requires that the characteristics of society in the 21st century be able to overcome challenges through learning. It examines teachers' bravery for the challenges: Professional teachers who have easy access to information about cyberspace in 21st century society dream of reinforcing the phenomenon of poor quality education. Professional teachers impart science, technology, performance, and ethics to students. The challenge for 21st-century professional teachers is to educate students in science and technology, based on their age, through a disciplined, creative, innovative, and competitive approach to reach the Scientific Curriculum 2013. The parents of the students are expected to participate in the committee to support the acceleration and speed of educational progress. Due to this changed view of students as objects, the topic of the learning process becomes the starting point for discovering a variety of innovative learning approaches. Teachers need to be able to choose learning models that encourage each student's enthusiasm for actively participating in their learning experiences. An alternative learning model that allows students to develop thinking skills (thinking, communication, and connections) in solving problems is problem-based learning (PBL) to improve students' critical thinking skills. This is the background of why I am at the 11O Pekanbaru Elementary School did research. This study aims to investigate whether the application of the problem-based learning model can be used to improve the thinking skills of students in the VB 110 SD Negeri Pekanbaru.Key Words: Problem based learning (PBL) Critical Thinking Skills.